Enzimas do metabolismo da sacarose em cultura celular de Bauhinia forficata; Curcuma zedoaria e Phaseolus vulgaris - Mello, Marcia Ometto de; Amaral, Antônio Francisco de Campos; Melo, Murilo (Pesquisa Agropecuaria Brasileira, 2001)
The objective of this work was to study the activity of sucrose metabolizing enzymes in extracts of cell suspension cultures of Bauhinia forficata Link, Curcuma zedoaria Roscoe and Phaseolus vulgaris L. Invertase pathway was identified in the three studied species. Sucrose synthase pathway was also responsible for sucrose metabolism in Curcuma zedoaria and Phaseolus vulgaris cells. Activity values higher than 300 nmol min-1 mg-1 of protein were found for acid and neutral invertases, UDPglucose pyrophosphorylase and phosphoglucomutase in the cell extract of the three plant species. Sucrose synthase showed low activity in Bauhinia forficata cells. As sucrose concentration in the culture medium decreased, sucrose synthase activity increased in C. zedoaria and P. vulgaris cells. The glycolytic enzymes activity gradually reduced at the end of the culture period, when carbohydrate was limited.